2021
DOI: 10.1016/j.csbj.2021.08.051
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of the circadian clock and drug pharmacology to optimize irinotecan administration timing in colorectal cancer

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 75 publications
(132 reference statements)
1
34
0
Order By: Relevance
“…CRC cell lines display a variety of circadian phenotypes which range from a completely disrupted clock to less dramatic alteration in circadian rhythms, which have been reported in published work [ 8 , 9 , 23 , 24 , 25 ]. This variability can also be observed when evaluating the connection between the circadian clock and cancer-related pathways, and the effects are often specific for certain cell lines, as well as specific core-clock gene disruptions [ 8 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRC cell lines display a variety of circadian phenotypes which range from a completely disrupted clock to less dramatic alteration in circadian rhythms, which have been reported in published work [ 8 , 9 , 23 , 24 , 25 ]. This variability can also be observed when evaluating the connection between the circadian clock and cancer-related pathways, and the effects are often specific for certain cell lines, as well as specific core-clock gene disruptions [ 8 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer, and the second leading cause of cancer death worldwide [ 22 ]. Several studies demonstrated the inter-connection between circadian rhythms and cancer, including CRC [ 8 , 9 , 23 , 24 , 25 , 26 ]. Taking into consideration the lack of knowledge regarding Cynara cardunculus leaf extracts and the circadian clock, in the present study we aimed to investigate if putative anti-cancer effects of C. cardunculus may be related to an underlying circadian regulation in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In another setting, namely a breast cancer xenograft model, the efficacy of erastin, an inhibitor of xCT cystine/glutamate transporter, was improved when administered during the light phase when compared to the dark phase [ 114 ]. In the coming years, pharmacokinetics studies should take this into account, to define the optimal timing of anticancer drug delivery [ 115 ].…”
Section: Current Challenges and Perspectives: How To Define The Most ...mentioning
confidence: 99%
“…We think they are complementary because they characterize the dynamics of the DC vaccination at different levels. This strategy has been used in other data-driven computational models (Sobotta et al, 2017, Hesse et al, 2021, Fey et al, 2015.…”
Section: Model Calibration Using Experimental Datamentioning
confidence: 99%